Effects of two types of task instructions on literary text comprehension and motivational and affective factors. (August 2016) - Henschel, Sofie; Meier, Christel; Roick, Thorsten
Abstract: This experimental study investigated the effects of two types of task instructions on text comprehension, motivation, and emotional involvement. In all, 226 9th graders in low academic tracks were randomly assigned to complete reader-oriented (RO), text-based (TB), or no tasks after reading literary texts to elaborate their mental text representation. Whereas RO tasks encouraged emotional engagement and indirectly stimulated text analysis through creative activities, TB tasks focused on cognitive activity and directly encouraged text analysis. After students completed the tasks, they answered test items on content- and form-related text comprehension. The results indicate that form-related comprehension improved when students elaborated their mental text representation through TB tasks. By contrast, RO students were more interested in the tasks, and they showed slightly more emotional involvement. As the two types of task instructions seemingly have different effects, they may be considered complementary elements in instructional practices for lower academic tracks. Highlights: Weaker readers receive specific benefits from text-based and reader-oriented tasks. Weaker readers improve in form-related text comprehension under text-based instructions. Creative reader-oriented tasks contribute to motivation and emotional involvement. Combining reader-oriented and text-based instructions may be useful for teaching.